Posterior Reversible Encephalopathy Syndrome in Patients With Cancer. (1st June 2015) - Singer, Samuel; Grommes, Christian; Reiner, Anne S.; Rosenblum, Marc K.; DeAngelis, Lisa M.
Abstract : Background: Posterior reversible encephalopathy syndrome (PRES) is characterized by neurologic symptoms with typical lesions on neuroimaging and may be associated with chemotherapy and immunosuppressive agents used in patients with cancer. We described the spectrum of PRES at a major cancer center. Methods: We reviewed charts of adults with PRES between 2005 and 2011 at Memorial Sloan Kettering Cancer Center for clinical information and outcome. Results: We identified 21 women (68%) and 10 men (median cohort age: 58 years). Solid tumors ( n = 22, 71%) were more common than hematologic ( n = 8) or primary brain malignancies ( n = 1). Prior brain irradiation (16%) and central nervous system metastases (10%) were uncommon. There were 55% who received chemotherapy or targeted therapy within the month preceding PRES, including 6 patients who received bevacizumab; PRES followed allogeneic stem cell transplantation in 5 (16%). Presenting symptoms included confusion (71%), seizure (58%), and headache (48%). Maximum systolic and diastolic blood pressures were similar among patients grouped by cancer type, chemotherapy or bevacizumab use, and atypical imaging. Moreover, 37% of patients with both magnetic resonance imaging (MRI) and computed tomography (CT) had normal CT concurrent with PRES on MRI, and 84% returned to neurologic baseline at a median of 7.5 days (range: 1–167 days) from onset. Successful anticonvulsant taper was achieved in 51%. Chemotherapy rechallenge was attempted in 41% without recurrent PRES. Autopsy revealed nonspecific changes isolated to radiographically affected areas in one of two patients. Conclusion: Recent chemotherapy, particularly bevacizumab, is common in cancer patients with PRES. Clinical and radiographic presentations may vary; MRI appears more sensitive than CT. Anticonvulsant taper and chemotherapy rechallenge is often possible. Implications for Practice: Posterior reversible encephalopathy syndrome is characterized by neurologic symptoms with typical lesions on neuroimaging and may be associated with chemotherapy and immunosuppressive agents used in patients with cancer. Clinical and radiographic presentations are protean, and magnetic resonance imaging is more sensitive than computed tomography. Recovery is common, and many patients can be successfully rechallenged with the apparently offending chemotherapy agent or regimen. Abstract : Posterior reversible encephalopathy syndrome may be associated with chemotherapy and immunosuppressive agents used in patients with cancer. Clinical and radiographic presentations are protean, and magnetic resonance imaging is more sensitive than computed tomography. Recovery is common, and many patients can be successfully rechallenged with the apparently offending chemotherapy agent or regimen.